2016
DOI: 10.1016/j.cmet.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Adult NG2-Glia Are Required for Median Eminence-Mediated Leptin Sensing and Body Weight Control

Abstract: While leptin is a well-known regulator of body fat mass, it remains unclear how circulating leptin is sensed centrally to maintain energy homeostasis. Here we show that genetic and pharmacological ablation of adult NG2-glia (also known as oligodendrocyte precursors), but not microglia, leads to primary leptin resistance and obesity in mice. We reveal that NG2-glia contact the dendritic processes of arcuate nucleus leptin receptor (LepR) neurons in the median eminence (ME) and that these processes degenerate up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 62 publications
(90 reference statements)
10
126
0
1
Order By: Relevance
“…Interestingly, postnatally born hypothalamic neurons in rodents appear to be localized throughout the parenchyma rather than just near the ventricular zone (Kokoeva et al, 2007). It is therefore possible that quiescent neural progenitors reside in the parenchyma as well (Djogo et al, 2016), and might represent a stem cell or progenitor pool that is distinct from tanycytes.…”
Section: Source Of Adult Neurogenesismentioning
confidence: 99%
“…Interestingly, postnatally born hypothalamic neurons in rodents appear to be localized throughout the parenchyma rather than just near the ventricular zone (Kokoeva et al, 2007). It is therefore possible that quiescent neural progenitors reside in the parenchyma as well (Djogo et al, 2016), and might represent a stem cell or progenitor pool that is distinct from tanycytes.…”
Section: Source Of Adult Neurogenesismentioning
confidence: 99%
“…In line with this view, confocal and electron microscopy studies showed that NG2 glia establish physical contacts with functionally relevant neuronal domains, including dendrites [41,42], somata [14,41,43,44], nodes of Ranvier [45,46] and synapses [47,48] (Figure 1C). About 30-50% of the nodes are contacted by both NG2 glia and astrocyte processes in the optic nerve, corpus callosum, and spinal cord of young adult rodents.…”
Section: Introductionmentioning
confidence: 68%
“…In line with this view, confocal and electron microscopy studies showed that NG2 glia establish physical contacts with functionally relevant neuronal domains, including dendrites [41,42], somata Figure 1. Schematic representation of the mechanisms assuring NG2 glia maintenance and of their physical interactions with neurons and other central nervous system (CNS) cell types (A) NG2 glia are distributed in a grid-like manner and occupy non-overlapping domains.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations